All Days 2016
DOI: 10.2118/179603-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flooding Economics, from Pilot to Field Implementation at the Example of the 8 TH Reservoir, Austria

Abstract: As polymer injection has not reached the same maturity as waterflooding, implementing polymer injection projects at field scale requires a workflow comprising screening of the portfolio of an organization for oil fields potentially amenable for polymer injection, laboratory and field testing followed by sector- and field implementation and roll-out in the portfolio. Going through the workflow, not only the subsurface uncertainty is reduced but also the knowledge about the cost structure and oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Incremental oil production is the result of injection of polymers decreasing the mobility of the injected water. For larger scale projects, one of the main cost drivers is the costs of the polymer (Sieberer et al 2016). The effectivity of the injected polymers to increase oil production can be measured by defining a Utility Factor (UF) ϭ kg of polymers injected / incremental bbl oil produced (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Incremental oil production is the result of injection of polymers decreasing the mobility of the injected water. For larger scale projects, one of the main cost drivers is the costs of the polymer (Sieberer et al 2016). The effectivity of the injected polymers to increase oil production can be measured by defining a Utility Factor (UF) ϭ kg of polymers injected / incremental bbl oil produced (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing recent studies evaluating the economics of polymer flooding it can be concluded that OPEX described above is generally underestimated (Alkhatib, 2015;AlSofi and Blunt, 2011;Behr, Olie, Visser & Leonhardt, 2013;Botechia, Correia & Schiozer, 2016;Mogollón, Tillero, Gutiérrez & Luján, 2016;Raniolo, S., Dovera, L., Cominelli, A., Callegaro, C., and Masserano, F., 2013;Sieberer et al, 2016). Mogollón and Lokhandwala (2013) presented an example of polymer flood economics using a broad range of costs to potentially cover high OPEX based on a probabilistic approach.…”
Section: Summary Discussionmentioning
confidence: 99%
“…Deployment of a polymer project requires that the incremental oil production revenue overcome the CAPEX and OPEX of the polymer project. Sieberer et al (2016) reported in an in-depth economic analysis that (a) polymer cost, (b) central facility, and (c) drilling & completion of wells have a considerable influence on the net present value. Thus, a reduction of the injected polymer amount improves the project economy.…”
Section: Mechanism Of Polymer Floodingmentioning
confidence: 99%